Method development and validation of simultaneous estimation of miconazole and metronidazole in tablet dosage form RP -HPLC method - B.Jyothsna; V. Swapna (International Journal of Pharmacy and Analytical Research, 2017)
A new simple, accurate, precise isocratic high performance liquid chromatographic (HPLC) method was developed and validated for the determination of miconazole and metronidazole in tablet formulation. The optimized conditions comprise of column C18,150mmx4.6, 5 mm particle size with a flow rate of 1.0 mL/min, Mobile Phase: 0.1%OPA: Methanol (75:25) mixture was used at a detection wavelength 268 nm. Retention times of miconazole and metronidazole were found to be 2.87min, and 3.75 min respectively. The method was validated in terms of linearity, accuracy, precision, specificity, LOD and LOQ. The LOD values of miconazole and metronidazole were found to be 0.01 and 0.014 µg/mL, LOQ’s were found to be 0.03 and 0.04µg/mL respectively. Method is linear in the range of 50 to 150%. This new method was successfully developed and validated as per ICH guidelines, can be utilized for the quantitative estimation of miconazole and metronidazole pharmaceutical dosage forms.